Energy, society and environment : technology for a sustainable future. - Elliott, David, 1943- (London : Routledge, 2003)
Whilst energy use is fundamental to human existence, it is also at the heart of many environmental problems we face in the 21st century. Deteriorating air quality and the global warming phenomenon can all be attributed to our use of fossil fuels. The re-emergence of nuclear power as an alternative also prompts major concerns. Sustainable alternatives such as wind and hydroelectric power also face opposition. Energy, Society and Environment explores the ways in which energy interacts with society and the environment. The book is structured to provide: an understanding of energy related environmental problems an appreciation of the strengths and weaknesses of technological solutions knowledge of the social and institutional obstacles to implementing these solutions an understanding of the strategic issues facing sustainable energy use. The revised edition reflects recent changes in the area. Chapters on nuclear and wind energy have been revised in response to recent debates. Coverage of fossil fuels has also been strengthened, whilst there is greater emphasis on environmental and energy policy in the context of the debate surrounding the Kyoto accord. Additional case-studies have been added which highlight alternative energy solutions. Energy, Society and Environment examines the potential and limits of technological solutions to energy-related environmental problems and suggests that social, economic and political solutions may also be necessary to avoid serious environmental damage in the future. Global case studies are used throughout to ground the debates and illustrate the interaction between technological and social aspects.
Keywords: Duurzame energie